The Effect of Imagery Speed of a New Motor Task on Performance Duration - Ali Fathizadeh; Hasan Mohammadzadeh Jahatlo (University of Tehran, 2013)
Motor imagery is the ability to imagine performing a movement without any action. The time a movement is mentally rehearsed highly correlates with the actual time of motor action. In this study, the effect of voluntary changes in imagery speed on the duration of the actual performance and learning a complex unfamiliar skill, and also the difference between the effects of real-time and fast imagery were investigated. 32 male volunteers (mean age: 22.23±2.07 yr) participated in the pretest, imagery training period, posttest, and retention test. The motor task was a sequence of new skills involving coordinated movements of upper and lower extremities with body locomotion. During the training period and in the real time, they mentally rehearsed the sequence performed in the pretest faster and more slowly. Analysis of variance (ANOVA), dependent and independent t tests were used to analyze the data. The findings revealed that the actual duration of real-time and fast imagery group decreased after training period (p<0.05) and it did not change in the retention test compared with the posttest (p>0.05). However, there was no difference between the effect of real-time and fast imagery (p>0.05). Moreover, no significant differences were found in the subsequent performance and retention of control and slow imagery groups (p>0.05). It is suggested that the duration of motor imagery should be close to the duration of physical performance in order to promote the performance and learning new tasks and individuals should be cautious about changes in mental image speed.